(untitled) (CIPEEX, 2022)
ACCESSIBILITY GOES BEYOND GUARANTEEING THE RIGHT TO BECOME ATTRACTIVE TO A CONDITION OF PHYSICAL OR PSYCHIC WEAKNESS. THIS TERM IS STILL MISUNDERSTOOD. IN ADDITION, THIS IS ONE OF THE REPORTS OF GUARANTEE OF FREE CONTACT, INTERACTION AND SOCIALIZATION, AS WELL AS THE FREEDOM OF ACCESS TO OTHERS AND THE FREEDOM TO INTERACT WITH THEM. THE PRESENT WORK WAS COMPOSED OF TWO SONGS THAT REPRESENT LOVE, EMPATHY, BROTHERHOOD AND FRATERNITY, QUALITIES THAT ARE INTRINSIC AND EVERYDAY. CULTURAL POSES ARE METHODS THAT GUIDE THE MOMENTS OF INTROSPECTION, GENERATING A METAMORPHOSIS OF PERSONALITIES. THE TWO SONGS CHOSEN WERE VOCALIZED LIVE, IN A SIX-MINUTE INTERVAL, WITH THE SCOPE OF A SPECIAL MOMENT. FOR EXAMPLE, A PRESENTATION SOUGHT TO EMPHASIZE FREE INTERPERSONAL RELATIONSHIPS, WITHOUT RESTRICTIONS AND DIFFERENCES, WAS NOT A LEARNING CHANNEL BUT A SOLUTION THAT HINDERS UNDERSTANDING FOR PERSONAL EMPOWERMENT.THE WORDS OF CHRIST ARE RELATED TO IMMORTAL VALUES. SOCIETY IS INCREASINGLY PREOCCUPIED WITH TRANSCENDENT ASPECTS OF LIFE. ALL THINGS IN THE COSMOS ARE FACED WITH AN ONGOING PROCESS OF METAMORPHOSIS AND GROWTH, PROGRESS BEING ONE OF LIFE’S DESIGNS. HONESTY PRESENTS THE LESSONS PREACHED BY THE SERMONS OF OUR EXISTENCE, WITH INTRINSIC CHANGES, EXTERIORIZING THE WORLD. THE OBJECTIVE OF THE WORK WAS TO STIMULATE ACTS OF HONESTY, HIGHLIGHTING THE VALUE OF THIS QUALITY. THROUGH THE ASSEMBLY OF A BULLET SALE STAND SOUGHT TO INCITE HONESTY. THE DIFFERENCE WAS IN THE FACT THAT THERE WAS NO ONE RESPONSIBLE FOR THE SALES LOGISTICS. IN THIS WAY, THE CUSTOMER AND OTHER PEOPLE WHO PASSED THE STAND WERE FORGED TO ACT CORRECTLY. WE PUT 10 UNITS OF BULLETS. IN THE END, ALL WERE SOLD AND THE CORRECT VALUE INSIDE THE BOX. THUS, THE WORK WHISPERED IN THE EARS OF THE SPECTATORS THE NEED TO RECOVER NON-NEGOTIABLE VALUES, TO BE BETTER, TO MAKE A DIFFERENCE IN THE SOCIAL CIRCLE AND TO IMPACT LIVES. THE MONETARY VALUE COLLECTED WAS EARMARKED FOR PHILANTHROPIC PROJECTS.&NBSP; KEYWORDS:VIRTUES.LEARNING. PESSOAL AUTONOMY.